Selenium status in blood, urine, and hair samples of newly diagnosed pediatric cancer patients - Karaman, Serap; Mansuroglu, Banu; Kizilbey, Kadriye; Derman, Serap; Hazar, Afife Binnaz (Tubitak Scientific & Technological Research Council Turkey, 2015)
Background/aim: Selenium (Se) is a trace element that has multiple functions. Low Se amounts in serum and hair have been reported in pediatric and adult cancer patients. The aim of our study was to evaluate Se levels in the serum, urine, and hair of pediatric cancer patients with leukemia, lymphoma, and solid tumors when compared with healthy children. Materials and methods: The concentrations of Se in the serum, hair, and urine of 32 Turkish children as healthy controls and 88 Turkish children diagnosed with acute leukemia (58), lymphoma (16), and solid tumors (14) were measured using inductively coupled plasma mass spectroscopy. Results: Se levels in the serum and hair of the children with cancer were significantly lower than those of the controls. There were no differences between the leukemia, lymphoma, and solid tumors group. On the other hand, the Se levels of the urine samples were slightly elevated in cancer patients compared with the control group. There was no marked difference in the Se levels of patients with different types of cancer. Conclusion: Se deficiency might be associated with the development of pediatric cancer. Especially in children, additional studies are needed to define whether low levels of Se may play a role in cancer pathogenesis.
Keywords: Childhood; leukemia; lymphoma; solid tumor; selenium; ACUTE LYMPHOBLASTIC-LEUKEMIA; SERUM SELENIUM; TRACE-ELEMENTS; CHILDREN; ZINC; DISEASE; HEALTH; RISK; LUNG; General & Internal Medicine